2017
DOI: 10.1007/s00717-017-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal C3F8 gas in patients with vitreomacular traction

Abstract: SummaryBackground We aimed to assess the efficacy of a single intravitreal perfluoropropane (C3F8) gas injection for the treatment of vitreomacular traction with or without a macular hole. Methods In this retrospective case series, seven eyes of six patients with symptomatic vitreomacular traction documented on optical coherence tomography, one with a macular hole additionally, received a single intravitreal C3F8 gas injection of up to 0.3 ml. The primary endpoint was vitreomacular traction release at 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…No systemic complications occurred in our study, which is in line with previous studies who have not reported any systemic complications either 15 21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No systemic complications occurred in our study, which is in line with previous studies who have not reported any systemic complications either 15 21 .…”
Section: Discussionsupporting
confidence: 93%
“…The gas bubble should liquefy the vitreous body during the gas expansion and induce the cortical vitreous to collapse during the absorption phase of the bubble, leading to PVD. Recent studies have shown PVD rates ranging from 40 to 88.6% depending on the intravitreal gas administered 16 21 . In the present study, we analyzed the outcomes after a single 0.3 ml C3F8 gas injection as a treatment for VMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation